Hubungan Indeks Massa Tubuh dengan Kejadian Kanker Prostat dan Gleason Score di Rumah Sakit Siloam Kupang - Valerio Christopher Homalessy; Shintia Christina; Erma Mexcorry Sumbayak (Jurnal MedScientiae, 2022)
Prostate cancer can be termed as the most commonly diagnosed cancer in men. The risk of prostate cancer increases with age. Knowing whether there is a relationship between Body Mass Index (BMI) with prostate cancer and gleason score at Siloam Hospital Kupang. Methods, qualitative research method with cross sectional design and using secondary data from medical records with consecutive sampling technique. Results, patients diagnosed with prostate cancer at Siloam Hospital for the 2017-2021 period were 80 cases and 60 cases were not prostate cancer. The BMI in the group of prostate cancer patients was 54 people (67.5%) in the non-obese group and 34 people (56.67%) in non-prostate cancer. The most cases of prostate cancer with histopathological degrees of High Gleason Score were 45 cases (56.25%), and histopathological degrees of Low Grade Score were 35 cases (43.75). The chi square analysis, it is known that there is no relationship between BMI and the incidence of prostate cancer having a p value = 0.189 (p > 0.05) and the Gleason Score has a p value = 0.764 (p > 0.05). Conclusion there was no relationship between BMI and the incidence of prostate cancer and gleason score at Siloam Hospital Kupang.